Dietary carotenoids change the colour of Southern corroboree frogs. (19th May 2016) - Umbers, Kate D. L.; Silla, Aimee J.; Bailey, Joseph A.; Shaw, Allison K.; Byrne, Phillip G.
Abstract : Animal coloration can be the result of many interconnected elements, including the production of colour‐producing molecules de novo, as well as the acquisition of pigments from the diet. When acquired through the diet, carotenoids (a common class of pigments) can influence yellow, orange, and red coloration and enhanced levels of carotenoids can result in brighter coloration and/or changes in hue or saturation. We tested the hypothesis that dietary carotenoid supplementation changes the striking black and yellow coloration of the southern corroboree frog ( Pseudophryne corroboree, Amphibia: Anura). Our dietary treatment showed no measurable difference in colour or brightness for black patches in frogs. However, the reflectance of yellow patches of frogs raised on a diet rich in carotenoids was more saturated (higher chroma) and long‐wave shifted in hue (more orange) compared to that of frogs raised without carotenoids. Interestingly, frogs with carotenoid‐poor diets still developed their characteristic yellow and black coloration, suggesting that their yellow colour patches are a product of pteridines manufactured de novo .